Life Cycle Energy Consumption and Greenhouse Gas Emissions of Polylactic acid (PLA) and Polystyrene (PS) Trays - Unchalee Suwanmanee; Thanawadee Leejarkpai; Yosita Rudeekit; Thumrongrut Mungcharoen (Agriculture and Natural Resources, 2010)
This study aimed to assess the energy consumption and greenhouse gas (GHG) emissions of three types of materials used for tray production in Thailand. The materials studied were a polystyrene (PS) tray produced in Thailand and derived from petroleum, a polylactic acid (PLA-baseline) tray, which was produced in the USA and derived from corn, with the third one being a PLA tray with process improvement (PLA-improved). The improvements to the hypothetical PLA-improved tray included using PLA pellets produced in Thailand, using biomass feedstocks for PLA pellet production and reducing the amount of raw materials used in the forming process. The functional unit (FU) was 1,000 units of trays, with each tray being 20 × 14 × 1.5 cm. The first part of the study considered the production of PS trays, PLA trays (PLA-baseline) and PLA trays with process improvement (PLA-improved). The energy consumption and GHG emissions of PLA-improved trays was 51.38% and 63.2% lower than that of PS and PLA-baseline trays, respectively. Consequently, PLA-improved trays generated lower GHG emissions than PS trays by 16.04%, but the energy consumption to produce PLA-improved trays was slightly higher (4.06%) than that for PS trays. In the second part of the study, different waste management scenarios using PS, PLA-baseline and PLA-improved trays were considered. It was found that incineration with energy recovery was suitable with PS trays because it could reduce energy consumption and GHG emissions by 22.7% and 3.4%, respectively, whereas, composting and landfill with energy recovery from methane collection were suitable with PLA-baseline and PLA-improved trays. Composting of PLA-baseline and PLAimproved trays produced a reduction in energy consumption of 6.5% and 12.0%, respectively, while GHG emissions were reduced by 267.7 and 253.9 kg CO2 equivalent/FU, respectively. Landfill with energy recovery from methane collection from PLA-baseline and PLA-improved trays resulted in energy consumption reductions of 17.2% and 31.8%, respectively, with reductions in GHG emissions of 138.3 and 114.3 kg CO2 equivalent/FU, respectively.